2012
DOI: 10.7243/2050-2389-1-1
|View full text |Cite
|
Sign up to set email alerts
|

The First Genetic Map and Positions of Major Fruit Trait Loci of Bitter Melon (Momordica charantia)

Abstract: Albeit extensive cultivation of bitter melon both as vegetable and medicine in many countries of Asia, Africa, and South America, no serious efforts have been made for genetic and breeding studies on this 'orphan' crop. In contrast to popular cucurbits, it lacks a genetic linkage map as required for genomic depiction and precise breeding. We report here on the construction of the first genetic linkage map of bitter melon using a set of 146 F2 progenies derived from an inter-botanical variety cross between Taiw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 16 publications
0
36
0
Order By: Relevance
“…The construction of a genetic map is a common approach to detect QTLs and conduct gene mapping. The first genetic map of bitter gourd was constructed based on amplified fragment length polymorphism (AFLP) markers ( Kole et al, 2012 ). A year later, the second genetic map was constructed, and it consisted of combined markers including simple sequence repeats (SSR), AFLP, and sequence-related amplified polymorphism (SRAP) markers ( Wang and Xiang, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The construction of a genetic map is a common approach to detect QTLs and conduct gene mapping. The first genetic map of bitter gourd was constructed based on amplified fragment length polymorphism (AFLP) markers ( Kole et al, 2012 ). A year later, the second genetic map was constructed, and it consisted of combined markers including simple sequence repeats (SSR), AFLP, and sequence-related amplified polymorphism (SRAP) markers ( Wang and Xiang, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a larger population (203 individuals) was used, giving greater reliability to the data. Kole et al (2012) constructed the first genetic map for bitter melon (Momordica charantia) by mapping an F 2 population consisting of 146 individuals, solely based on 108 AFLP markers, covering 3060.7 cM of the genome. Lanteri et al (2006) developed a reference genetic map for artichoke (Cynara cardunculus) in which a population consisting of 94 F 1 individuals was used, based on 59 different primers (SSRs, AFLPs, and SSAPs), and covering 2569.9 cM of the genome.…”
Section: Resultsmentioning
confidence: 99%
“…To date, there is no precise report on QTL mapping for any trait in bitter gourd and only few studies have been reported. Kole et al (2012) mapped five of each qualitative and five quantitative trait loci by using AFLP markers; Wang and Xiang (2013) did the genetic linkage map for 13 horticulture traits by RAD-seq analysis; Matsumura et al (2014) identified one SNP marker, GTFL-1 linked to the gynoecious locus at a distance of 5.46 cM and Cui et al (2018) identified SNP markers relate to sex expression, fruit epidermal structure and fruit color. In our present study, we applied high throughput GBS technology with type-II restriction endonuclease ApeKI (GCWGC) ( Elshire et al, 2011 ) to identify SNPs in F 2 and F 2:3 segregated populations for economically important traits like, sex and earliness in bitter gourd.…”
Section: Discussionmentioning
confidence: 99%
“…The first genetic map and positions of major fruit trait loci of bitter melon were worked out by Kole et al (2012) . An extensive genetic linkage map was constructed for bitter gourd via the study of F 2:3 progenies derived from two cultivated inbred lines ( Wang and Xiang, 2013 ).…”
Section: Introductionmentioning
confidence: 99%